(untitled) (Revista de Investigaciones Universidad del Quindío, 2021)
Marketing satisfies human needs and wants through goods, services and ideas. The protection of the environment and ecosystems is important to guarantee access to basic resources, health, favorable environments for economic and leisure activities and to improve people’s quality of life. This work analyzes local, governmental and civil society actions, from 2003 to 2020, for the rescue and preservation of the Magdalena River, CDMX. Five types of actions were analyzed: cleaning, sanitation, resource management, urban improvement, diffusion and environmental culture from the approaches of government marketing, social causes and sustainability. This approach helped identify needs, interests and trends associated with the rescue of the river by the government and civil society. As a result, the need for impact evaluations was determined. One of the proposed methodologies is the Theory of Change (ToC) that helps to detonate the dialogue between actors, know their opinions, needs and promote the strategic co-creation of impact routes integrating the actions of government and society.